IMPLEMENTATION AND SUPERVISION OF OFFICIAL DISCRETION IN LOCAL GOVERNMENT OF REPUBLIC OF INDONESIA - ishak, nurfaika (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2019)
Abstract Discretion is particularly vulnerable to the misuse of authority by officials which could lead to collusion, corruption and nepotism and made the administration of government no longer aims for public’s benefit and interest but for the advantage of a few and conflict interest of corrupt people. Therefore, the clear procedures related to the implementation for supervision of the discretion, especially on local government in the the Republic of Indonesia.This study aims to provide a more in-depth understanding of the issues of implementation and supervision of discretion of government officials. The form of legal research used in this study is juridical-normative research. Juridical-normative legal research consists of research on principles, systematics, and legal synchronization. This study also based on laws and regulations related to the implementation and supervision of discretion by officials. This study shows that every official of the state administration in performing their duties shall be based on legitimate authority, which is provided by laws and regulations. Governance should be based on law (wet matigheid van bestuur = legality principle = le rincile de la egalite de'l administration). The supervision of the discretion of government officials is prohibited to the abuse of authority. Government Officials are prohibited from misusing authority. Supervision is carried out by internal control apparatus. The results of supervision are: no errors; there are administrative errors; or there are administrative errors with a financial loss to the state. Keywords: Discretion, Supervision, Local Government.